Forest health an integrated perspective - Castello, John D., 1952-; Teale, Stephen A. (Cambridge University Press, 2011)
"Forest Health: An Integrated Perspective is the first book to define an ecologically rational, conceptual framework that unifies and integrates the many sub-disciplines that comprise the science of forest health and protection. This new global approach applies to boreal, temperate, tropical, natural, managed, even-aged, un-even aged and urban forests, as well as plantations. Readers of the text can use real datasets to assess the sustainability of four forests around the world. Datasets for the case studies are at www.cambridge.org/9780521766692, and the text provides stepwise instructions for performing the calculations in Microsoft Excel. Readers can follow along as the editors perform the same calculations and interpret the results. Elevating forest health from a fuzzy concept to an ecologically sound paradigm, this is essential reading for undergraduate and graduate students and professionals interested in forest health, protection, entomology, pathology and ecology"--